Beyond Engagement: Using Storyboards as a Digital Storytelling Tool for Teaching Libyan EFL University Students Literary Fiction During the Covid-19 Pandemic - Mohamed, Fatma (مجلة كلية الاداب, 2022)
In the current situation of COVID-19 pandemic, and in response to an appeal from the Libyan Ministry of Education to all universities and colleges to improve the quality of education as the country is in lockdown, there are new ongoing discussions on how best to integrate technology for online-learning and teaching. How best to address the academic rigor of the new situation in Libyan EFL university classrooms during this period of unexpected and unprecedented educational disruption, and to engage students in meaningful use of technology for learning is a topic of great interest to practitioners and researchers alike. By encouraging online or blended learning, language institutions are making great efforts to further promote the foreign language learning process. Integrating technology into the EFL curriculum is not a single concept which is generated from a single theory, and its implementation calls for a range of perspectives and theoretical views. This paper discusses the issue of technology’s contribution in EFL classroom, more specifically it investigates the teaching of literary fiction and how best to support its reading and understanding through technology. The question raised in this paper is how technology facilitates the attainment of course goals. So, it tries to propose answers to the questions: How can we best make use of technology for planning literary lessons? What instructional strategies can teachers use to promote reading development? How do teachers help their students acquire the necessary skills for literary analysis and understanding in an online environment? The aim of this research paper is therefore to provide suggestions which Libyan EFL classrooms could make use of in the current situation, to promote technology use and online learning when teaching literature, and also make use of this technology to promote understanding, and analysis of literary texts (fiction) in order to develop creativity, collaboration, and eventually language skills. It, therefore, proposes the utilization of digital storytelling tools like ‘StoryboardThat’ as an instructional approach to facilitate art-based language standards